Effects of sustained natural apophyseal glides versus rocabado 6 x 6 program in subjects with cervicogenic headache - Murtza, Sadia; Noor, Rabiya; Bashir, Muhammad Salman; Ikram, Mehwish (BMC musculoskeletal disorders, 2024)
Background Cervicogenic headache is designated as the most common type of secondary headache that results from conditions affecting the neck's bony components, muscles, and intervertebral discs rather than the head itself. Objective The purpose was to determine the effects of Sustained Natural Apophyseal Glides (SNAGs) versus the Rocabado 6 x 6 program in subjects with cervicogenic headaches. Methods This study was a randomized clinical trial. The sample size was 38, and participants aged 20-60 years (mean age 40.22 [+ or -] 9.66) suffering from cervicogenic headaches were randomly allocated using the lottery method into two groups with 19 participants in each group. Assessment of subjects was done before starting treatment and by the end of the 8th week for all the variables. Outcome measures were the Neck Disability Index (NDI), 6-item Headache Impact Test (HIT-6), Flexion-Rotation test (FRT) to assess the rotation range of motion at the level of C1-C2 (goniometer) and the Numeric Pain Rating Scale (NPRS) for the intensity of pain. Data analysis was done by SPSS (IBM) 25. To check the normality of the data the Shapiro-Wilk test was used. Results In the Shapiro-Wilk test p-value of all the testing variables i.e. NDI, HIT-6 score, FRT and NPRS was > 0.05, data was normally distributed and parametric tests were used. Group A showed a considerable improvement (p < 0.05) in all variables compared to Group B, while within-group analysis of both groups shows that all outcome measures show significant results (p < 0.05). Conclusion It was concluded that both SNAGs and Rocabado's 6 x 6 exercises were effective for the treatment of cervicogenic headache but the effects of headache SNAG were superior and produced more improvement in intensity of headache, disability, frequency of headache, duration of headache as compared to Rocabado 6 x 6 exercises. Trial registration number This study was registered at ClinicalTrials.gov ID: NCT05865808 on date 19/05/2023. Keywords: Cervicogenic headache, Mobilization, Pain, Range of motion, Temporomandibular disorders